2017
DOI: 10.18632/oncotarget.15388
|View full text |Cite
|
Sign up to set email alerts
|

Skip lateral lymph node metastasis leaping over the central neck compartment in papillary thyroid carcinoma

Abstract: ObjectiveThis study was performed to investigate the frequency and pattern as well as the predictive factors of skip metastasis (lateral cervical lymph node metastasis without central lymph node metastasis) in papillary thyroid carcinoma (PTC).Methods450 PTC patients who received total thyroidectomy with central neck dissection(CND) combined with modified radical lateral neck dissection(LND) were divided into two groups: with or without skip metastases. The clinicopathological characteristics were statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
65
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 31 publications
(59 reference statements)
15
65
3
Order By: Relevance
“…In the univariate analyses, we found that age, primary tumor location and primary tumor size≦1cm were significantly related with skip metastasis in PTC patients (all P 0.05). These variables were also the independent predictors of skip metastasis, and their predictive value was verified by multivariate analysis, while gender, total tumor size, tumor extension, multifocality, bilaterality, ETE, HT, capsule invasion were not significantly association with skip metastasis((all P 0.05)(tables 2 and 3), In this study, Patients with primary tumor location in the upper portion were more likely to have skip metastasis, which is in line with previous reports [13,16,24]. This predictive factor could be explained by the anatomical structure of the lymphatic drainage system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the univariate analyses, we found that age, primary tumor location and primary tumor size≦1cm were significantly related with skip metastasis in PTC patients (all P 0.05). These variables were also the independent predictors of skip metastasis, and their predictive value was verified by multivariate analysis, while gender, total tumor size, tumor extension, multifocality, bilaterality, ETE, HT, capsule invasion were not significantly association with skip metastasis((all P 0.05)(tables 2 and 3), In this study, Patients with primary tumor location in the upper portion were more likely to have skip metastasis, which is in line with previous reports [13,16,24]. This predictive factor could be explained by the anatomical structure of the lymphatic drainage system.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the primary tumor size not larger than 1cm was more frequent in skip metastasis (54.55% vs.35.33%, P =0.013), these results may remind us that the primary tumor size is important factor for predicting skip metastasis, we should be carefully evaluated lateral lymph nodes status when tumor size no larger than 1cm. Previous literatures also revealed that skip metastasis was more common in less aggressive forms of PTC [16].…”
Section: Discussionmentioning
confidence: 82%
“…Skip metastasis is a well-known form of metastatic spread to regional lymph nodes and has a positive effect on prognosis in non-small-cell lung cancer and colorectal cancer [ 19 , 20 ]. However, a recent study analyzed the survival rates of 450 PTC patients between 39 patients exhibiting skip metastasis and 411 patients without skip metastasis [ 21 ]. The results showed no significant difference between the two groups for tumor free survival.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in accordance with the ethical standards of the World Medical Association Declaration of Helsinki. PTC diagnoses, surgical procedures and postoperative follow-up protocols were performed as described in our previous studies [ 21 , 22 ]: all patients accepted the initial follow-up at 1 month after surgery. The main items investigated were TSH, FT3 and FT4 levels in all cases, and Tg and TgAb in total thyroidectomy cases, which were assessed at the 1-month follow-up, and then every 3 months during the first year followed by every 6 months thereafter.…”
Section: Methodsmentioning
confidence: 99%